2018
DOI: 10.3390/ijms19020534
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Cleavage by Topoisomerase 2: A Mark of the Core Centromere

Abstract: In addition to its roles in transcription and replication, topoisomerase 2 (topo 2) is crucial in shaping mitotic chromosomes and in ensuring the orderly separation of sister chromatids. As well as its recruitment throughout the length of the mitotic chromosome, topo 2 accumulates at the primary constriction. Here, following cohesin release, the enzymatic activity of topo 2 acts to remove residual sister catenations. Intriguingly, topo 2 does not bind and cleave all sites in the genome equally; one preferred s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Human TOP2A recognizes and cleaves within the single-stranded DNA loop region of the hairpin structure formed within alpha satellite DNA ( 36 ), and human TOP2B binds and cleaves four-way junction DNA structure ( 34 ). Site-specific cleavage by TOP2 at centromeric DNA with dyad symmetries (potential to form hairpins and four-way junctions) is found in yeast, fruit fly, chicken and human ( 35 , 37 ). Moreover, mismatched bases which are often present in multiple stem-loop structures, when in the proximity of TOP2 cleavage sites can greatly stimulate TOP2 cleavage activity and hinder DNA end re-ligation ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human TOP2A recognizes and cleaves within the single-stranded DNA loop region of the hairpin structure formed within alpha satellite DNA ( 36 ), and human TOP2B binds and cleaves four-way junction DNA structure ( 34 ). Site-specific cleavage by TOP2 at centromeric DNA with dyad symmetries (potential to form hairpins and four-way junctions) is found in yeast, fruit fly, chicken and human ( 35 , 37 ). Moreover, mismatched bases which are often present in multiple stem-loop structures, when in the proximity of TOP2 cleavage sites can greatly stimulate TOP2 cleavage activity and hinder DNA end re-ligation ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies demonstrate a major contribution of TOP2 activity in the generation of DSBs in highly transcribed genes ( Canela et al, 2019 ; Gittens et al, 2019 ; Gothe et al, 2019 ). Moreover, several studies demonstrated that DNA topoisomerase 1 (TOP1) and TOP2 recognize and preferentially cleave DNA at regions forming stable secondary structures ( Froelich-Ammon et al, 1994 ; Jonstrup et al, 2008 ; Mills et al, 2018 ; West and Austin, 1999 ). In eukaryotic cells, TOP1 and TOP2 activities are required to resolve topological stresses resulting from DNA transactions (for a review, see Pommier et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…TOP2 responds to torsional stress generated in the maintenance of the genome; however, supercoiling is not required and TOP2 does not have a stringent recognition sequence [67,68]. Interestingly, there is evidence that alternative DNA secondary structures are targeted by topoisomerase for enzymatic cleavage (Figure 2A) [69,70,71,72]. Specifically, Froelich-Ammon et al demonstrated that TOP2 can recognize and cleave stem-loop structures one nucleotide from the 3′ base of the stem structure [69].…”
Section: Alternative Dna Secondary Structures and Unusual Bases Prmentioning
confidence: 99%
“…Additionally, TOP2 was shown to cleave the single-stranded loop of stem-loop structures formed in alpha-satellite sequences. This activity is seen in the alpha-satellite contained in centromeres across multiple species, which further points to a non-B DNA secondary structure as the common site for TOP2 cleavage [70,71]. Furthermore, West and Austin demonstrated that TOP2B not only binds and cleaves four-way junction DNA, but also has on average a four-fold higher affinity for four-way junction DNA compared to linear DNA [72].…”
Section: Alternative Dna Secondary Structures and Unusual Bases Prmentioning
confidence: 99%
See 1 more Smart Citation